2020
DOI: 10.2147/ijn.s249622
|View full text |Cite
|
Sign up to set email alerts
|

<p>Size-Dependent Interactions of Lipid-Coated Gold Nanoparticles: Developing a Better Mechanistic Understanding Through Model Cell Membranes and in vivo Toxicity</p>

Abstract: Introduction: Humans are intentionally exposed to gold nanoparticles (AuNPs) where they are used in variety of biomedical applications as imaging and drug delivery agents as well as diagnostic and therapeutic agents currently in clinic and in a variety of upcoming clinical trials. Consequently, it is critical that we gain a better understanding of how physiochemical properties such as size, shape, and surface chemistry drive cellular uptake and AuNP toxicity in vivo. Understanding and being able to manipulate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
47
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 99 publications
(128 reference statements)
4
47
0
3
Order By: Relevance
“…When comparing spherical hybrid-lipid-coated AgNPs (10 nm) to triangular-shaped (32 nm) particles, the spherical hybrid lipid-coated AgNPs were determined to be more toxic than triangular-shaped AgNPs, suggesting that the size and shape of the AgNPs contribute to toxicity in embryonic zebrafish (Danio rerio) [72]. Studies with similar hybrid lipid-coated gold nanoparticles (AuNPs) of 5, 10, and 20 nm in zebrafish embryos showed rapid toxicity with 5 nm AuNPs and significant mortality occurring at concentrations ≥20 mg/L compared to the 10 nm and 20 nm AuNPs, which showed no significant mortality throughout the 5-day experiment [73]. Using model membranes and sum-frequency gain (SFG) spectroscopy, Engstrom et al showed that 5 nm and 10 nm AuNPs can phase into the lipid monolayer with very little energetic cost; whereas 20 nm AuNPs warped the membrane conforming it to the curvature of hybrid lipid-coated AuNPs [73].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…When comparing spherical hybrid-lipid-coated AgNPs (10 nm) to triangular-shaped (32 nm) particles, the spherical hybrid lipid-coated AgNPs were determined to be more toxic than triangular-shaped AgNPs, suggesting that the size and shape of the AgNPs contribute to toxicity in embryonic zebrafish (Danio rerio) [72]. Studies with similar hybrid lipid-coated gold nanoparticles (AuNPs) of 5, 10, and 20 nm in zebrafish embryos showed rapid toxicity with 5 nm AuNPs and significant mortality occurring at concentrations ≥20 mg/L compared to the 10 nm and 20 nm AuNPs, which showed no significant mortality throughout the 5-day experiment [73]. Using model membranes and sum-frequency gain (SFG) spectroscopy, Engstrom et al showed that 5 nm and 10 nm AuNPs can phase into the lipid monolayer with very little energetic cost; whereas 20 nm AuNPs warped the membrane conforming it to the curvature of hybrid lipid-coated AuNPs [73].…”
Section: Introductionmentioning
confidence: 99%
“…Studies with similar hybrid lipid-coated gold nanoparticles (AuNPs) of 5, 10, and 20 nm in zebrafish embryos showed rapid toxicity with 5 nm AuNPs and significant mortality occurring at concentrations ≥20 mg/L compared to the 10 nm and 20 nm AuNPs, which showed no significant mortality throughout the 5-day experiment [73]. Using model membranes and sum-frequency gain (SFG) spectroscopy, Engstrom et al showed that 5 nm and 10 nm AuNPs can phase into the lipid monolayer with very little energetic cost; whereas 20 nm AuNPs warped the membrane conforming it to the curvature of hybrid lipid-coated AuNPs [73]. Because the 5 nm have a lower energy barrier to cross the membrane, their uptake is greater and could lead to the increased toxicity observed [73].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking this feature, smaller sized contrast agents excreted through the kidney are suitable as functional renal contrast agents, while larger sized are found better suited for blood and lymphatic imaging. The similar phenomenon of size effect also exist in gold nanoparticles (11) and iron oxide (12). Like those nano and sub-micron materials, particle size of silk broin will potentially in uence its blood clearance, metabolic pathways, and metabolic rate, especially when silk broin takes spherical shape in biomedical applications.…”
Section: Introductionmentioning
confidence: 78%
“…Inorganic nanoparticles can be engineered to possess useful physiochemical properties for use in applications including biomedicine and diagnostics [ 1 , 2 , 3 , 4 , 5 , 6 ]. While shape [ 7 ] and size [ 8 ] both play critical roles in defining nanoparticle properties, surface chemistry is likewise crucial for function and colloidal stability [ 9 , 10 ]. The nanoparticle surface interfaces with the external environment, and appropriately engineered surfaces can be used to regulate interactions between nanoparticles and biomolecules [ 11 ] including peptides [ 12 ], proteins [ 13 ] and nucleic acids [ 14 ].…”
Section: Introductionmentioning
confidence: 99%